Iatrogenic ventricular fibrillation caused by inappropriately synchronized cardioversion in a patient with pre-excited atrial fibrillation: A case report - Ikeda, Syuhei (J Cardiol Cases, 2020)
Direct-current (DC) cardioversion is effective at terminating arrhythmias in an emergency. During treatment, energy delivery synchronizing with the QRS complex is essential to avoid ventricular fibrillation (VF) caused by a shock on the T wave, which is the vulnerable period of ventricular repolarization. However, distinguishing the QRS from the T wave is difficult in some patients with abnormal, irregular, and varying QRS complexes. We report the case of a 45-year-old man who had iatrogenic VF caused by inappropriate synchronization with the T wave during cardioversion of pre-excited atrial fibrillation due to high ventricular rates and varying R wave amplitude affected by an accessory pathway. <Learning objective: During direct-current cardioversion, energy delivery synchronizing with the QRS complex is essential to avoid ventricular fibrillation (VF) caused by a shock on the T wave. However, distinguishing the QRS from the T wave is difficult in some patients with abnormal, irregular, and varying QRS complexes. We report a case of iatrogenic VF caused by failed synchronization with the R wave in a patient with pre-excited atrial fibrillation (AF). Clinicians managing pre-excited AF should be aware of the possibility of iatrogenic VF triggered by cardioversion.>